Molecular cloning and functional expression of the first two specific insect myosuppressin receptors. - Egerod, K.; Reynisson, E.; Hauser, F.; Cazzamali, G.; Williamson, M.; Grimmelikhuijzen, C.J.P. (Proceedings of the National Academy of Sciences of the United States of America, 2003)
The Drosophila Genome Project database contains the sequences of two genes, CG8985 and CG13803, which are predicted to code for G protein-coupled receptors. We cloned the cDNAs corresponding to these genes and found that their gene structures had not been correctly annotated. We subsequently expressed the coding regions of the two corrected receptor genes in Chinese hamster ovary cells and found that each of them coded for a receptor that could be activated by low concentrations of Drosophila myosuppressin (EC50,4 x 10(-8) M). The insect myosuppressins are decapeptides that generally inhibit insect visceral muscles. Other tested Drosophila neuropeptides did not activate the two receptors. In addition to the two Drosophila myosuppressin receptors, we identified a sequence in the genomic database from the malaria mosquito Anopheles gambiae that also very likely codes for a myosuppressin receptor. To our knowledge, this paper is the first report on the molecular identification of specific insect myosuppressin receptors.